Influence of health literacy on health promoting behaviour of adolescents with and without obesity - Kehinde O. Adewole; Adesola A. Ogunfowokan; Monday Olodu (Elsevier, 2021)
Background: Learning has been associated with human behaviour, and health literacy is vital in an individual's health promotion and maintenance activities. Purpose: This study aimed at comparing the health literacy and health-promoting behaviour of adolescents with and without obesity, and to also identify the association between health literacy and health-promoting behaviour of these two groups of adolescents. Methods: A concurrent mixed-method design was adopted and the study was conducted among150 adolescents with obesity and 150 adolescents without obesity from 15 private secondary schools in Osun State, Nigeria. A structured self-administered questionnaire and an in-depth interview guide were used to collect data on their health literacy levels and health-promoting behaviour. Results: The findings showed that adolescents without obesity had a higher level of health literacy (70%) compared to their counterparts with obesity (59%). More than half (55.3%) of those with obesity and 35% of those without obesity scored low on health-promoting behaviour scale. Also, there was a significant relationship between health literacy and health-promoting behaviour among adolescents with obesity (r = 0.29; p = 0.001) and those without obesity (r = 0.85, p = 0.015). Conclusion: The study concluded that adolescents with obesity had lower level of health-promoting behaviour despite their high level of health literacy, compared to those without obesity. Irrespective of the adolescent's obesity status, their health-promoting behaviour is significantly associated with their health literacy. Implication for school nursing practice is documented.